Inflammatory myofibroblastic tumor of kidney with heterotopic bone formation: An unusual case mimicking a renal malignancy - Navale, Pooja (Medknow Publications & Media Pvt Ltd, 2013)
Inflammatory myofibroblastic tumor (IMFT) or pseudotumor is a rare tumor that can be seen in various organs. It is an enigmatic tumor of unknown etiology and difficult to differentiate from malignancy, clinically as well as radiologically. Histologically, it is composed of variable proportions of proliferating spindle myofibroblasts, fibroblasts, extracellular collagen, lymphocytes and plasma cells. This mainly affects the urinary bladder or prostate. Renal involvement is extremely rare and may pose diagnostic difficulty to the clinician. We describe a renal IMFT, mimicking renal malignancy, having unusual histological features.